Applied sport, exercise, and performance psychology : current approaches to helping clients - Tod, David; Eubank, Martin; Routledge (Firm) (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Applied sport, exercise, and performance psychology practice has diversified considerably over the years, as consultants have explored various theoretical models to guide them in helping their clients. Applied Sport, Exercise, and Performance Psychology: Current Approaches to Helping Clients provides in-depth and critical coverage, from a global perspective, of the common approaches practitioners now use with clients. Chapters are supplemented with case studies showing the approaches in action. The text explores topics such as: evidence-based practice, psychodynamics approaches, family systems approaches, mindfulness, cognitive behavioural approaches, practitioner training and development, cultural considerations in practice. The comprehensive companion website is designed to facilitate a flipped classroom approach using case studies, role play scenarios, and practice exercises, suggested essay and exam questions and topics, and webcasts from the authors. This text is a vital resource for students in BPS accredited applied sport psychology courses, sport and exercise science courses, and psychology and counselling courses. It is also an invaluable read for practicing applied sport, exercise, and performance psychologists, as well as coaches and parents with some background in psychology"--
Theoretical orientations in service delivery / David Tod, Martin Eubank, and Britton W. Brewer -- Psychodynamic approaches / Fernanda Serra de Queiroz and Mark Andersen -- Person-centred approaches / Jonathan Katz and Julie Keyes -- Cognitive therapy approaches / Martin Eubank, Robert Morris, and Matthew Cunliffe -- Mindfulness approaches / Mark B. Andersen and David E. Williams -- Existential approaches / Mark S. Nesti and Noora J. Ronkainen -- Family therapy approaches / Michael Zito -- Cognitive behavioural therapy in performance enhancement: Using exposure and behavioural experiments with elite athletes / Henrik Gustafsson and Carolina Lundqvist -- Brief consultations in sport and performance psychology / Jessyca Arthur-Cameselle and Burt Giges -- Life skills interventions with elite athletes / Adam Miles and Ken Hodge -- Developing an integrated approach / David Tod and Moira Lafferty -- Cultural considerations in practice / Stephanie J. Hanrahan and Sae-Mi Lee -- Evidence-based practice / David Tod and Judy Van Raalte -- Practitioner development: Adopting and adapting service delivery approaches / R.I. (Vana) Hutter and J. R. (Rob) Pijper.
OCLC-licensed vendor bibliographic record.
Keywords: Sports -- Psychological aspects; Exercise -- Psychological aspects; Physical fitness -- Psychological aspects; Coaching (Athletics); SPORTS & RECREATION / Sports Psychology; PSYCHOLOGY / Applied Psychology; HEALTH & FITNESS / General